2023
DOI: 10.1590/1678-5150-pvb-7150
|View full text |Cite
|
Sign up to set email alerts
|

Searching bovine papillomavirus presence in lesions seen on teats of cows

Abstract: The samples were taken from 106 cows with various-looking lesions on their teats and ranged in age from 2 to 8 years. Enzyme-linked immunosorbent assay (ELISA) antigen (Ag) positive for the bovine papillomavirus (BPV) was found in 59 (55.7%) blood serum samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
0
0
Order By: Relevance
“…However, BPV DNA has been detected in horses' sarcoid mass and it has been suggested that flies (Musca autumnalis) carrying BPV DNA can act as vectors for BPV transmission (Kemp-Symonds, 2000). BPV generally spreads through direct or indirect contact, entering the skin through abrasions and lesions (Özmen and Kale, 2023). Therefore, in the case we examined, we suspect that inter-species transmission of BPV occurred through direct contact or via flies.…”
Section: Discussionmentioning
confidence: 98%
“…However, BPV DNA has been detected in horses' sarcoid mass and it has been suggested that flies (Musca autumnalis) carrying BPV DNA can act as vectors for BPV transmission (Kemp-Symonds, 2000). BPV generally spreads through direct or indirect contact, entering the skin through abrasions and lesions (Özmen and Kale, 2023). Therefore, in the case we examined, we suspect that inter-species transmission of BPV occurred through direct contact or via flies.…”
Section: Discussionmentioning
confidence: 98%